The association between hospitalization for asthma in childhood and alcohol use disorder hospitalization during adolescence and early adulthood among males in an Australian birth cohort - Liang, Wenbin; Chikritzhs, Tanya (Informa Healthcare, 2013)
Objective: Associations between asthma and a range of mental disorders have been increasingly reported from cross-sectional studies. The aim of this study is to investigate whether hospitalization for asthma during childhood is associated with an increased risk of hospitalization for alcohol use disorders during adolescence and early adulthood. Method: This study used a population-based birth-cohort design and included males (n = 56369) born between 1980 and 1984 in Western Australia (WA). Hospitalizations for asthma and alcohol use disorders were identified using ICD-9 codes and ICD-10 codes. Survival analysis and multivariate Poisson regression model were used in the analysis. Results: The risk of alcohol use disorder hospitalization was significantly higher among participants who had been hospitalized for asthma during ages 3–6 years and 12–18 years. Conclusion: In this cohort study of Western Australian males, hospitalizations for asthma during childhood were associated with an increased risk of alcohol use disorder hospitalization among males.